Language Socialization of Written Academic Discourse - Dwi Wulandari (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
This paper will look at the studies conducted to see how written academic discourse is socialized. Written academic discourse socialization is a dynamic process, mostly socially situated and comtemporarily involves multimodal, multilingual, and intertextual context. This paper will see what influences the process of language socialization within this context, focusing on how the novice learners learn to participate themselves into the academic written discourse. In different setting of culture, there are various values that learners bring into educational context. The same thing also happens in the socialization of written discourse. Learners bring their previous experiences, shaped identity, and other values that might be different, or even in contrast with what is being socialized. In this way, it is interesting to see how learners cope with such things and take the step to participate in the academic world. Equally important, it is necessary to examine the impact of language socialization forms, either in the form of feed back, remodelling, or criticism on the learners resistance or conformity